Adoption of new-media marketing in the green industry - Yao, Becatien (Kansas State University, 2016)
Nurseries and garden centers face challenges to stay economically viable, particularly in rural areas. Their efforts to advertise horticultural products through traditional methods seem insufficient to increase their sales. Marketing through new media is receiving more attention by businesses across various industries. In order to assess whether this growing interest in new-media is applicable to the green house industry, it is important to determine their impact on business performance and the factors driving its adoption. Few studies report the impact of social media on nurseries and garden centers performance. The literature on technology adoption shows that network and learning effects play a critical role in agricultural technology adoption (Bandiera and Rasul, 2006; Baerenklau, 2005), while perceived ease of use and perceived usefulness have been identified as the major factors of adoption of information technology (Davis, 1989; Lorenzo-Romero et al., 2014). This study builds on the known factors of agricultural and information technology adoption to determine the key variables affecting the extent of use of new-media marketing in the green industry. Using a survey, data were collected from 161 nurseries and garden centers across the United States. Results indicate that the network effect had a robustly, positive effect on the extent of use of new-media marketing in the green industry. The estimated network effect was statistically significant in the models using frequency of online marketing use, frequency of social media use and hours of social media use as the respective dependent variables measuring the use of new media. Other statistically significant factors include the percentage of retail sales, the perceived usefulness, and the city population. The study also found that new-media marketing, measured by the number of hours spent on social media, had a positive impact on sales for nurseries and garden centers making more than $200,000 a year. By providing evidence of new-media marketing effectiveness, these results contradict the belief that sales do not increase immediately after a social media campaign, suggesting a low return on investment. Besides this evidence, the magnitude of the network effect and the differences in critical factors driving adoption across firm size are key information to tailor training programs and make informed policy decisions to support marketing efforts.
Keywords: New-media marketing; Green industry; Nursery; Garden center; Social media; Adoption